PENGARUH INDEPENDENSI, KOMPETENSI, DAN PROFESIONALISME TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI (Studi Empiris pada Auditor Internal BPKP di Jawa Tengah) - Yolanda Esperanza Nugroho, 13.05.52.0035; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of independency, competency,and profesionalisme on audit quality which auditor ethics is moderated. Especially in teh internal auditor working on the BPKP in Central Java. The population in this study were all auditors working on the BPKP in Central Java. Sampling was done using method random sampling which Disproportionate stratified random sampling and sample size were 72 respondents. The primary data collection method used survei method was used a questionnaire . Data were analyzed using technical analyze Moderate Regression Analyze (MRA). The result showed that the independency, competency, and profesionalisme affect the quality of the audit. And for moderation variable between independency and auditors ethics influence to quality of audit. While competency variable and profesionalisme variable with auditor ethics have no effect on quality audit.Keywords: Independency, Competency, Profesioalisme, Auditors Ethics, Quality of Audit